On the digital republishing of Ukrainian literary classics - Vladyslav Mukha (Енциклопедичний Вісник України)
This communication examines the creation and implementation of a series of interconnected online encyclopedias dedicated to the works of prominent Ukrainian figures: Taras Shevchenko, Ivan Franko, Mykhailo Hrushevsky, and Lesia Ukrainka. These digital resources have significantly contributed to Ukrainian culture and literature. The author offers an in-depth look at the technological framework of the project, including the content management system, website structure, and tools for searching and analyzing information. Attention is also given to the process of populating the sites with content and evaluating user traffic. Finally, the review outlines a vision for the project’s future development, highlighting plans for expansion and enhancement.